Evaluation of pharmacological and non-pharmacological methods of smoking cessation; A Review - Nandita Gautam; Shivalingesh KK; Swati Sharma; Resham Irshad; Satyaki Verma (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Objective: Tor review the pharmacologic and non-pharmacological therapies of smoking cessation.  During recent years, there have been many advances in different types of pharmacological and non‑pharmacological tobacco cessation treatments. This paper reviews the established pharmacological methods such as nicotine replacement therapy (NRT) (patches, gum, sublingual tablets, lozenges, inhalers and nasal spray) and drugs such as Bupropion and Varenicline and non-pharmacological methods such as counselling and yoga (Sudarshan kriya, Kapalbhati, Anuloma-viloma and Bhramari pranayama).